PENINGKATAN KINERJA USAHA MELALUI PEMBENAHAN MANAJEMEN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) PADA INDUSTRI KULINER - Agrina, Camelia Rizki; Kirana, *Desty Hapsari (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2023)
Jawa Barat memiliki UMKM terbesar di bidang industri kuliner. Sebagian besar UMKM terkena dampak pandemi covid sehingga terjadi penurunan omset penjualan. Hal ini menjadi dorongan bagi UMKM untuk bertahan dengan cara mengelola usahanya lebih baik. Pelatihan dan pendampingan yang dilakukan ini adalah untuk menjawab keresahan UMKM dalam menghadapi kondisi pandemi covid. Peserta pelatihan mayoritas masih kesulitan dalam pengelolaan manajemen usahanya. Sehingga UMKM diberikan pelatihan terkait dengan pengelolaan pada aspek pemasaran, produksi, manajemen organisasi dan legalitas usaha serta keuangan. Berdasarkan hasil pelatihan, UMKM yang sebelumnya tidak memiliki pencatatan keuangan, menjadi bisa melakukan pencatatan keuangan yang menghasilkan laporan keuangan yakni neraca usaha dan laporan laba rugi. Selain itu, pada aspek produksi dan manajemen organisasi pun UMKM bisa mengatur produksi dan organisasinya lebih baik. Pada aspek pemasaran, UMKM dapat memanfaatkan teknologi sebagai media promosi usahanya. West Java has the largest MSMEs in the culinary industry. Most MSMEs were affected by the covid pandemic resulting in a decrease in sales. This is a challenge for MSMEs to survive by managing their business better. The objective of the training was to answer the concerns of MSMEs in dealing with the conditions of the covid pandemic. The majority of training participants still have difficulties in managing their business management. So that MSMEs are trained related to management in the aspects of marketing, production, organizational management and business legality and finance. Based on the results, MSMEs, which previously did not have financial statements, are now able to carry out financial statements, namely a balance sheet and income statement. In addition, in terms of production and organizational management, MSMEs can better manage production and organization. In the marketing aspect, MSMEs can utilize technology as a tool for promoting their business West Java has the largest MSMEs in the culinary industry. Most MSMEs were affected by the covid pandemic resulting in a decrease in sales. This is a challenge for MSMEs to survive by managing their business better. The objective of the training was to answer the concerns of MSMEs in dealing with the conditions of the covid pandemic. The majority of training participants still have difficulties in managing their business management. So that MSMEs are trained related to management in the aspects of marketing, production, organizational management and business legality and finance. Based on the results, MSMEs, which previously did not have financial statements, are now able to carry out financial statements, namely a balance sheet and income statement. In addition, in terms of production and organizational management, MSMEs can better manage production and organization. In the marketing aspect, MSMEs can utilize technology as a tool for promoting their business.